2021
DOI: 10.3389/fimmu.2021.676173
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Causes Osteoarthritis-Like Transcriptional Changes in Human Osteoarthritis-Derived Chondrocytes and Synovial Fibroblasts In Vitro

Abstract: Increased interleukin (IL)-17A has been identified in joints affected by osteoarthritis (OA), but it is unclear how IL-17A, and its family members IL-17AF and IL-17F, can contribute to human OA pathophysiology. Therefore, we aimed to evaluate the gene expression and signalling pathway activation effects of the different IL-17 family members in chondrocytes and synovial fibroblasts derived from cartilage and synovium of patients with end-stage knee OA. Immunohistochemistry staining confirmed that IL-17 receptor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Interestingly, predictions showed that PRP molecules modulate IL-17 signaling. Recent data support a role for IL-17A in OA joints [45] and set the grounds to investigate this specific inflammatory phenotype. IL-17 in increased in obese and associated to obesity-related inflammatory comorbidities [46].…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, predictions showed that PRP molecules modulate IL-17 signaling. Recent data support a role for IL-17A in OA joints [45] and set the grounds to investigate this specific inflammatory phenotype. IL-17 in increased in obese and associated to obesity-related inflammatory comorbidities [46].…”
Section: Discussionmentioning
confidence: 89%
“…The pro-inflammatory cytokine IL-1β is one of the central pro-inflammatory cytokines in many diseases and activates various pathways leading to the progression of osteoarthritis [24,25]. IL-17, on the other hand, is crucially involved in changes to the transcriptome of chondrocytes, which has also been shown in studies of osteoarthritis patients [26,27]. In addition, IL-17 leads to an increase in TNF-α production [28], which is shown in our study within the group of simple cytokine treatments.…”
Section: Discussionmentioning
confidence: 94%
“…S 7 a). IL-17 cytokines have demonstrated pathophysiology in osteoarthritis in preclinical and clinical studies [ 25 ]. Quantification of Il17f mRNA in the draining inguinal lymph node increased in some mice in the saline and APS without cell treatment groups compared to the other groups, although did not reach statistical significance (Fig.…”
Section: Resultsmentioning
confidence: 99%